(untitled) (GIST – Education and Learning Research Journal, 2019)
This study examines future teachers’ theoretical reflections on Critical Incidents and how these link to Costa Rica’s English teaching system. Participants included 30 senior college students from an English teaching program. Using narrative research techniques, the authors have concluded that: (1) spaces for reflection must be created in EFL so that students’ voices are heard; (2) both instruction and assessment need to be tackled not from the native speaker angle but from the learner language perspective; and (3) because mistakes are both inherent to foreign language learning and an indicator of language development, more tolerance to learner errors needs to be exercised. The study proves relevant for language pedagogy and Applied Linguistics (AL) since it paves the way for further research, opens room for reflection and dialogue, and enhances our understanding of the issue at stake from a future-teacher standpoint.